Impact of Environmental, Social and Governance Indicators – ESG on Automotive Corporate Sustainability - del Carmen Garcia, Maria; Garcia, Sorely; Oliver, Javier; Tamosiuniene, Rima (Transformations In Business & Economics, 2026)
There has been a marked increase in stakeholder interest regarding the level of development of ESG criteria. This is reflected in the ESG score issued by various agencies. A high ESG score is associated with a company being more sustainable than another. It is imperative to analyse the relationship between different economic-financial variables of companies and their classification as a sustainable company. In this case, the objective is to analyse corporate financial sustainability in the automotive sector. For this purpose, a sample of 430 companies in the automotive sector was utilised. Different economic-financial variables corresponding to different dimensions such as liquidity, solvency, profitability and indebtedness were selected. Principal component analysis was used to condense the information provided by the different variables in each of the dimensions or factors. A stochastic Logit model is used to analyse the relationship between these factors and the financial sustainability of the companies. Conversely, the degree of financial sustainability, or financial sustainability index, can be determined by the coefficients of the Logit model transformed into an odds ratio. Consequently, the percentage variation in this index can be determined in the context of variations in each of the economic and financial factors. The findings indicate that, for this sector, an improvement in the ESG criteria means an increase in the financial sustainability index of around 72%. The factor related to solvency is also positively related. In this case, an improvement in the company’s solvency means a 30% increase in financial sustainability. On the other hand, an increase in the profitability factor leads to a 74% decrease in financial sustainability. Finally, an increase in indebtedness also leads to a 84% decrease in sustainability.